PERANCANGAN APLIKASI E-COMMERCE DENGAN METODE COLLABORATIVE FILTERING DAN APRIORI - Jacky Jacky; Desi Arisandi; Manatap Dolok Lauro (Fakultas Teknologi Informasi Universitas Tarumanagara, 2020)
This e-Commerce application is an application for Rajawali Electric Store. This application is made using Collaborative Filtering and Apriori method to recommend products from Rajawali Electric Store. This Application will give product recommendations based on user transactions and user rating. Transaction data used in Apriori method were taken from Rajawali Electric store transaction data, while rating data in Collaborative Filtering method were taken from several websites that have product rating. Results from Apriori method shows that with 50% support value, user that buys Recessed White 66664 and Bulb 19w CDL E27 A80 have the possibility of buying Bulb 14.5W E27 220-240V A67 with confidence value of 89.47%. Results from Collaborative Method produced different results based on users and types of products